NOtes on cylinder bridge piers and the well system of foundations especially written to assist those engage in the construction of bridges, quays, docks, river-walls, weirs, etc - Newman, John (E. & F.N. Spon, 1893)
Especially written to help those designing or erecting cylinder bridge piers and abutments, and concrete, brick or masonry wells, as applied to bridges, quay-, dock-, and river-walls, etc., many of the chapters have previously appeared as serial articles in The Engineering Review.